Kematangan Keselarasan Strategis Bisnis dan TI pada Lembaga Edukasi dan Konsultasi TI - Clara Hetty Primasari (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
The strategic alignment of business and Information Technology (IT) is an important element for an organization so that the organization can realize the benefits of information technology for the business they run. Technological advances, especially in the Industrial Revolution 4.0 era, made all organizations that wanted to win the competition not only implement technology in their business processes, but also had to align the use of information technology with non-IT units in the organization. The impact of the Industrial Revolution was felt in all fields, including education. In the midst of a lot of research on measuring the level of strategic alignment at higher education institutions, this research focuses on measuring the level of strategic alignment that has been carried out by institutions other than tertiary education, namely the IT Education and Consultation Institute in Yogyakarta. The model used in this alignment measurement is the Strategic Alignment Maturity Model (SAMM). From this research it is known that the IT Education and Consultation Institute which actively provides consulting and education services specifically in the IT field, understands the importance of Strategic Alignment in Business and IT and applies them in carrying out its business activities. However, despite implementing IT best practices as what has been taught to its customers, this institution needs to realize and improve the areas of IT human resources, business communication and IT, and measuring the value of benefits and IT competence.